Finite p-groups with some isolated subgroups - Janko, Zvonimir (Journal of algebra, 2016)
We say that a subgroup H is isolated in a group G if for each x∈G we have either x∈H or 〈x〉∩H={1}. Here we shall determine certain classes of finite nonabelian p-groups which possess some isolated subgroups (Theorems 1, 2, 4, 6 and 8 to 16).
Gesehen am 23.02.2018